Does the gender of the head of the household affect the labour m arket outcomes for females? A n empirical analysis for Pakistan based on Labour Force Survey (LFS 2017-2018) - Andlib, Zubaria; Sarfaz, Mudassira; Kamran, Muhammad (Publishing House of Wroclaw University of Economics and Business, 2022)
Higher women’s labour force participation (LFP), is a significant contributing factor in achieving economic growth, poverty reduction, and female empowerment. Although women’s LFP increased from 14% in 2001-02, to 20% in 2017-18, Pakistan is still lagging behind in women’s labour market participation compared to countries on a similar development ladder. The presented study explored the contributing factors of low female LFP in Pakistan for male and female-headed households separately, using the micro data set from Pakistan Labour Force Survey 2017-18. The empirical evidence for the contributing factors of female LFP suggests that urban women are less likely to be engaged in work activities. Women with higher education, from extended families and those who received vocational training, will engage more in labour market activities. Regarding the heads of households, the results reveal that women from female-headed households supply their labour services more than those from male-headed households. The authors infer from their analysis that due to gender norms and patriarchy at the household level, most women from male-headed households are not part of the labour force.
Argumenta Oeconomica, 2022, Nr 2 (49), s. 71-92
Keywords: women's LFP; female-headed household; Pakistan